2017
DOI: 10.1038/s41598-017-10517-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial colonization is required for normal neurobehavioral development in zebrafish

Abstract: Changes in resident microbiota may have wide-ranging effects on human health. We investigated whether early life microbial disruption alters neurodevelopment and behavior in larval zebrafish. Conventionally colonized, axenic, and axenic larvae colonized at 1 day post fertilization (dpf) were evaluated using a standard locomotor assay. At 10 dpf, axenic zebrafish exhibited hyperactivity compared to conventionalized and conventionally colonized controls. Impairment of host colonization using antibiotics also cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 59 publications
4
91
0
1
Order By: Relevance
“…Like Vibrio, Aeromonas species are abundant members of the zebrafish intestinal microbiota [35]. Previous studies suggest that these 2 genera naturally compete against one another within complex intestinal communities [39]. In addition, we have shown that Vibrio is capable of invading and displacing established Aeromonas populations in gnotobiotic animals [32].…”
Section: Loss Of Swimming Motility or Chemotaxis Attenuates Intestinamentioning
confidence: 81%
“…Like Vibrio, Aeromonas species are abundant members of the zebrafish intestinal microbiota [35]. Previous studies suggest that these 2 genera naturally compete against one another within complex intestinal communities [39]. In addition, we have shown that Vibrio is capable of invading and displacing established Aeromonas populations in gnotobiotic animals [32].…”
Section: Loss Of Swimming Motility or Chemotaxis Attenuates Intestinamentioning
confidence: 81%
“…Several tumors in humans are strongly associated with pathogenicity of a single bacterium, such as Helicobacter pylori [60], or are likely caused by interactions between two commensal bacteria, like Bacteroides fragilis and Escherichia coli [12]. Additionally, there is an accumulating evidence that commensal bacteria may support tissue homeostasis by, for instance, stimulating neurogenesis [61,62]. These observations point to the evolutionary conserved role of the host-associated bacteria in maintaining host tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, orally administered, non-absorbable antimicrobials have been used to alter the gut microbiome in rodents (neomycin, bacitracin, and pimaricin) [4][5][6] as well as in zebrafish (amphotericin, kanamycin, and ampicillin). 7 Behavioral changes similar to GF animals are reported with oral but not intraperitoneal 4 treatment particularly related to stress-associated and anxiety-associated phenotypes. Oral antibiotics have also been used to examine the contribution of the maternal gut microbiota during pregnancy to offspring behavior by maternal treatment either preconception (non-absorbable sulfonamide) 5 or early in gestation (neomycin, pimaricin, bacitracin).…”
Section: Behavioral Alterations In Animal Modelsmentioning
confidence: 90%